Membangkitkan Kewirausahaan di Masa Pandemi Covid-19 Melalui Keterampilan Pembuatan Motif Batik dengan Konsep Fraktal - Muhtarom Muhtarom; Sutrisno Sutrisno; Muhammad Saifuddin Zuhri; Duwi Nuvitalia (Pelita: Jurnal Pengabdian kepada Masyarakat, 2021)
During the Covid-19 pandemic like today, the majority of teenagers who are members of the RT 7 RW 9 Karangtaruna RT 7 RW 9 Kelurahan Gemah Pedurungan Semarang have been laid off and unemployed. This PKM activity aims to provide training for youth Karangtaruna RT 7 RW 9 Kelurahan Gemah Pedurungan Semarang City to have knowledge and skills in batik. The method used to achieve this goal is by training more demonstrations, question and answer and practice as well as mentoring. The training material is presented with more practice than theory, with a ratio of 25% theory and 75% practice. The expertise of the PKM team will be useful in training in batik skills, making batik motifs, making online marketing media implemented to PKM partners. The involvement of experts will be carried out to optimize the results of PKM activities. The results of PKM activities show that the level of understanding of the participants in the understanding of batik theory and business promotion through online media has increased. This is shown by the work produced by the community service participants.